Self rating of oral health status by student dental surgeon assistants in Ibadan, Nigeria – a pilot survey (2013)
Background: Individuals, generally, in this environment are known to rate their oral health status favourably despite the presence of oral diseases and conditions, probably due to sub optimal awareness level about oral health, however it is not known if this is the case with members of the dental team especially those who assist the dentist in day to day procedures. Objective: This study assessed the self ratings of oral health status amongst student dental surgeon assistants on clinical rotation at the Dental Centre, UCH, Ibadan. Method: This was a descriptive cross sectional study in which data was obtained with the use of self administered questionnaire and by clinical oral examination. Data obtained included sociodemographic data of respondents, questions assessing self rating of oral health status and evaluation of presence or absence of clinical oral conditions. Results: A total of 54 students with a mean age of 23.9years on clinical posting participated in the study. Nearly all (98.1%) rated their oral health as very good or good and 55.6% perceived a need for oral health care. About 60% had consulted a dentist previously. The mean DMFT was 0.28 and 14.8% of the respondents had a DMFT score > 0. Significant association was found between the global self rating of oral health and perceived need for dental treatment. Conclusion: The perceived need for dental treatment is an important factor in global rating of oral health amongst student dental surgeon assistants